VACUUM TOLERANCE OF TARDIGRADES (ABSTRACT) (16th Symposium on Polar Biology) - ウツギ, カズオ; ノダ, ヒロクニ; UTSUGI, Kazuo; NODA, Hirokuni (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper